2015
DOI: 10.1111/apm.12396
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus lugdunensis endocarditis following vasectomy – report of a case history and review of the literature

Abstract: Staphylococcus lugdunensis is a coagulase-negative Staphylococcus (CoNS), and part of the normal skin flora. The bacterium is an emerging pathogen that, unlike other CoNS, resembles coagulase-positive Staphylococcus aureus infections in virulence, tissue destruction, and clinical course. We report a fatal case following minor surgery. The frequency of S. lugdunensis infections has probably been underestimated and under-reported in the past as few clinical laboratories routinely identify coagulase-negative Stap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A total of 17 original published articles were considered appropriate for inclusion in our review article (Figure 1 ). Out of these 17 studies, 16 were case reports from Italy [ 5 , 6 ], Switzerland [ 7 ], USA [ 8 - 11 ], UK [ 12 , 13 ], Morocco [ 14 ], Taiwan [ 15 , 16 ], Saudi Arabia [ 17 ], Spain [ 18 , 19 ], and Norway [ 20 ] while one case series was from Greece [ 21 ]. Koh et al had reported the first case of S. lugdunensis endocarditis-associated CVA from London, UK in 1996 [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…A total of 17 original published articles were considered appropriate for inclusion in our review article (Figure 1 ). Out of these 17 studies, 16 were case reports from Italy [ 5 , 6 ], Switzerland [ 7 ], USA [ 8 - 11 ], UK [ 12 , 13 ], Morocco [ 14 ], Taiwan [ 15 , 16 ], Saudi Arabia [ 17 ], Spain [ 18 , 19 ], and Norway [ 20 ] while one case series was from Greece [ 21 ]. Koh et al had reported the first case of S. lugdunensis endocarditis-associated CVA from London, UK in 1996 [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…We fortuitously identified a heart valve infection occurring in a patient who had a recent vasectomy. Infective endocarditis possibly caused by vasectomy has been previously reported (23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…S. lugdunensis endocarditis has been associated with high mortality [15], although most of the S. lugdunensis isolates are sensitive to Penicillin G [13, 16]. High mortality is associated with the ability of the S. lugdunensis to cause tissue destruction leading to acute heart failure.…”
Section: Discussionmentioning
confidence: 99%